2018
DOI: 10.1097/bot.0000000000001246
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Complications Associated With MRI-Conditional External Fixators in Patients With Tibial Plateau Fractures: A Case Series

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…The results of this survey are consistent with previous reports of rare minor events (such as mild warmth and vibratory sensations) having occurred in a small number of patients, but no harmful complications or any lasting consequences. 6 Despite a lack of reported complications, heat generation during MRI scanning should be taken seriously, and it is possible that some of these events resulted in delayed complications, which were not appreciated by the attending orthopaedic surgeon completing the survey. However, heat generation of three of the most common, modern external fixation constructs during MRI scanning has been recently measured and, in most cases, did not exceed 1°C.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this survey are consistent with previous reports of rare minor events (such as mild warmth and vibratory sensations) having occurred in a small number of patients, but no harmful complications or any lasting consequences. 6 Despite a lack of reported complications, heat generation during MRI scanning should be taken seriously, and it is possible that some of these events resulted in delayed complications, which were not appreciated by the attending orthopaedic surgeon completing the survey. However, heat generation of three of the most common, modern external fixation constructs during MRI scanning has been recently measured and, in most cases, did not exceed 1°C.…”
Section: Discussionmentioning
confidence: 99%
“…The debate about the possibility to perform MRI in the presence of external fixator is more than 20 years old. After the safety concern has been largely investigated [ 1 , 7 , 8 , 14 ], the current discussion is about the efficacy of MRI in the presence of artifacts due to the presence of metallic component of external fixators. This study showed that, in the conditions described above, the MRI performed on instrumented legs provided images useful for more accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Gillig J.D. et al reported that MRI imaging in Schatzker IV, V and VI tibial plateau fractures better visualized bone landmarks and could avoid the use of computer tomography (CT), experiencing no complications [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations